Structure of hepatitis B Dane particle DNA before and after the Dane particle DNA polymerase reaction. - Hruska, J F (1977)
DNA isolated from the hepatitis B antigen form known as the Dane particle was examined by electron microscopy before and after the endogenous Dane particle DNA polymerase reaction. The most frequently occurring form was an untwisted circular double-stranded DNA molecule approximately 1 mum in length. Less frequently occurring forms included circular DNA of approximately unit length and having one or more small single-stranded regions, similar circular molecules with one or more tails either shorter or longer than 1 mum in length, and very small circular molecules with tails. There was no increase in frequency or length of tails after a DNA polymerase reaction, suggesting that tails were not formed during this reaction. The mean length of circular molecules increased by 23% when DNA was spread in formamide compared with aqueous spreading, suggesting that single-stranded regions are present in most of the molecules. The mean length of circular molecules obtained from aqueous spreading increased by 27% after a Dane particle DNA polymerase reaction. This indicates that single-stranded regions were converted to double-stranded DNA during the reaction.